2000
DOI: 10.1149/1.1393862
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Feature-Scale Surface Geometry on CMP Processes

Abstract: The influence of feature-scale surface pattern dimensions on chemical mechanical polishing (CMP) processes has been studied through numerical simulations using a discretized geometry approach. The development of planarity for a symmetrical 3 ϫ 3 array of square roughness elements with various lateral dimensions and spacing was simulated. Geometrical shielding of roughness elements by neighboring elements was found to cause asymmetrical surface polishing during the CMP processes. Given a specified trench spacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…[1][2][3][4][5] Current semiconductor fabrication technology for logic and memory devices requires CMP to achieve the required multilevel interconnection densities. [1][2][3][4][5] Current semiconductor fabrication technology for logic and memory devices requires CMP to achieve the required multilevel interconnection densities.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Current semiconductor fabrication technology for logic and memory devices requires CMP to achieve the required multilevel interconnection densities. [1][2][3][4][5] Current semiconductor fabrication technology for logic and memory devices requires CMP to achieve the required multilevel interconnection densities.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid mechanics: The effect of flowfield and hydrodynamic pressure of the slurry was not taken into account in this model. Past models have suggested that the slurry shear rate directly affects the wear of the wafer sample [1,26,27], while other studies have shown that the sample contact stress is affected by the slurry hydrodynamic pressure [35,36]. Neither of such assumptions are taken into account in the current model.…”
Section: Modeling Assumptionsmentioning
confidence: 97%
“…On the feature scale, studies by Chekina et al [21], Chang et al [22], Saxena et al [23], Nguyen et al [24], and Sawyer [25] have modeled dishing and erosion in CMP. Additionally, Yao et al [26,27] used shear-based wear modeling to predict the time evolution of surface features on a wafer sample.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical mechanical polishing (CMP) has the capability of achieving such stringent requirements over a step height of several microns. Since the introduction of the new technology in the 80s, the CMP provides advantages of defect reduction, wide windows for etching and lithography and yield improvement [5,6,13]. Combining the chemical reactions and mechanical force abrasion, the wafer surface can be polished to achieve global planarity.…”
Section: Introductionmentioning
confidence: 99%